Prof. Junichi Hiratsuka: BNCT may be able to benefit cancer patients in the near future - Li, Gin (Therapeutic Radiology and Oncology, 2018)
On Jan 27, the 3rd Annual Academic Conference of Taiwan Society of Neutron Capture Therapy was successfully held at Taipei Medical University.